Social Identity Transformation Among Remote Workers: A Phenomenological Study of the Millennial Generation in Indonesia - Padri, Abdul Robi (Al-Makki Publisher, 2025)
The advancement of digital technology and the global shift in work patterns have fostered the rise of remote work, a trend increasingly prevalent among the millennial generation in Indonesia. This transformation not only affects economic aspects and productivity but also brings significant consequences to the construction and transformation of workers’ social identities. This study aims to explore how the experience of remote work influences the social identity construction of millennials, including changes in social relationships, self-perception, and attachment to work communities. Using a phenomenological approach, the research involved in-depth interviews with ten participants aged 25 to 40 who have been working remotely for at least two years. The findings reveal that remote work initiates a complex process of identity renegotiation, in which millennials experience a shift in the meaning of workspace, the boundaries between personal and professional time, and the emergence of new, flexible, and digital forms of social connection. A dominant pattern of hybrid identity—combining the roles of “professional worker” and “free individual”—emerges, subtly influencing how individuals position themselves within the broader social structure. These findings highlight the importance of understanding identity dynamics in digital work contexts to formulate more inclusive and adaptive employment policies in response to ongoing social change.